2012
DOI: 10.1100/2012/498503
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Clay-Polymer Nanocomposites in Wastewater Pretreatment

Abstract: Some agricultural effluents are unsuitable for discharge into standard sewage-treatment plants: their pretreatment is necessary to avoid clogging of the filtering devices by colloidal matter. The colloidal stability of the effluents is mainly due to mutual repulsive forces that keep charged particles in suspension. Pretreatment processes are based on two separate stages: (a) neutralization of the charges (“coagulation”) and (b) bridging between several small particles to form larger aggregates that sink, leavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The obtained results showed that: (1) Overall, the dehydration and hydration process, the structure of Na + and/or Cs + saturated beidellite is characterized by a heterogeneous hydration state and presents numerous contributions of MLSs at the crystal scale more than those used for Na + and/or Cs + saturated montmorillonite specimens. (2) The investigation of MLSs content shows that the presence of Cs + cations in exchangeable sites is accompanied by a decrease of the hydration heterogeneities degree in smectite "crystallite", thus the Cs-saturated samples present a MLSs number lower than in the case of samples saturates with Na + cations. (3) The theoretical models related to the Cs-saturated smectites present a main structure with a major contribution of 0W and 1W layers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results showed that: (1) Overall, the dehydration and hydration process, the structure of Na + and/or Cs + saturated beidellite is characterized by a heterogeneous hydration state and presents numerous contributions of MLSs at the crystal scale more than those used for Na + and/or Cs + saturated montmorillonite specimens. (2) The investigation of MLSs content shows that the presence of Cs + cations in exchangeable sites is accompanied by a decrease of the hydration heterogeneities degree in smectite "crystallite", thus the Cs-saturated samples present a MLSs number lower than in the case of samples saturates with Na + cations. (3) The theoretical models related to the Cs-saturated smectites present a main structure with a major contribution of 0W and 1W layers.…”
Section: Resultsmentioning
confidence: 99%
“…As example: Rytwo et al [1] examined suitable nanocomposites based on different clays and polymers where the X-ray diffraction (XRD) measurements indicated that sequential addition of olive mill or winery effluents with a boosting dose of nanocomposites may yield a very efficient and rapid clarification pretreatment. Furthermore, Giora [2] presents in his study a nanocomposites, comprised of an anchoring particle and a polymer, as "coagoflocculants" and demonstrates that the use of such particles combines the advantages of coagulant and flocculant by neutralizing the charge of the suspended particles while bridging between them and anchoring them to a denser particle (the clay mineral), enhancing their precipitation.…”
Section: Introductionmentioning
confidence: 98%
“…They can also be merged into more complex structures having special characteristics. Clay polymer nanocomposite has been used for pretreatment of effl uents and removal of pollutants (Rytwo 2012 ).…”
Section: Nanocompositesmentioning
confidence: 99%
“…This situation has led toso significant interests in natural colorants and enlightening projects for an environmentally friendly improvement called as "green". So, recent studies have seen a number of attempts in development of nanopigments, because they are used in coating, plastics and printing inks and they offer many advantages such as photosensitivity and color strength [4,5]. Withregardtotheseadvances, numerous substances such as clay [5] andpolymer [6] have been used to synthesize "green" nanopigments.…”
Section: Introductionmentioning
confidence: 99%